Answer:
x = -2
Step-by-step explanation:
Answer: i guess the problem is with P(x) => "x =
", then P(x) is true if that equality is true, and is false if the equality is false.
so lets see case for case.
a) x = 0, and
= 0. So p(0) is true.
b) x = 1 and
= 1, so P(1) is true.
c) x = 2, and
= 4, and 2 ≠ 4, then P(2) is false.
d) x= -1 and
= 1, and 1 ≠ -1, so P(-1) is false.
The answer is on the picture!!
Answer:
Step-by-step explanation:
Add 4 to both sides
13 + 4 = w/-3 - 4 + 4
17 = w/-3 Multiply through by -3
17*-3 = -3*(w/-3)
-51 = w